Perilaku Sintaksis Verba Bahasa Banjar Hulu: Tinjauan Fungsi Gramatikal - Asnawi, Asnawi; Mukhlis, Muhammad (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
This present study explains about syntactiv verb of Banjar Hulu language: Review of Grammatical Functions. Banjar Language is a language used by the people of Indragiri Hilir Regency, Riau which has been neglected. Therefore, it is necessary to conduct the research of Banjar Hulu language to maintain that language especially the characteristics of verb. This study used descriptive method with data analysis focus on the form and function of verbs in sentences and relate them to distribution. The expected result of this research is the publication in unaccredited scientific journals of TKT 3. There were two findings of this study; first, transitive verb of Banjar Hulu language dominated by prefixes ma-, man-, and maN-kan. Based on these finding was found another transitive verb such ekatransitive, dwitransitive, and semitransitive. Second, intransitive verb Banjar Hulu language a lot of dominated by prefixes; ta-, ma-, and ba-.